Distortions of Normativity - Pauer-Studer, Herlinde (Ethical theory and moral practice, 2011)
We discuss some implications of the Holocaust for moral philosophy. Our thesis is that morality became distorted in the Third Reich at the level of its social articulation. We explore this thesis in application to several front-line perpetrators who maintained false moral self-conceptions. We conclude that more than a priori moral reasoning is required to correct such distortions.